Cyber Notary as A Mean of Indonesian Economic Law Development - Ikhsan Lubis; Tarsisius Murwadji; Sunarmi Sunarmi; Detania Sukarja (Sriwijaya Law Review, 2023)
This paper tries to show how Indonesian economic law has evolved via the emergence of the cyber notary idea. Notaries engage in various everyday tasks and activities in the fantastic world development, such as giving the clients the finest service possible and impacting the economy. According to the law, notaries are required to be able to help and support anyone who requires genuine written documentation of legal situations, events, or activities. This study employs qualitative approaches and descriptive analysis. Additionally, researchers are interested in the phenomenon that examines the idea of a cyber notary as a way to advance Indonesian commercial law. Qualitative research aims to conduct extremely thorough investigations that examine the research's findings in great detail. Both primary data and secondary data are employed as sources of information. The findings demonstrate that cyber notary adds value to electronic documents by legalising them, for example, in addition to digitising notarial operations. However, because many aspects need to be ready, its implementation will take some time. Article 1868 of the Indonesian Civil Code stipulates that a genuine deed is a deed in a certain form that has been prescribed by law and is made before a public authority.